Intrinsic Elements and Moral Values in Novel Tarian Bumi Karya Oka Rusmini (2007) - Ni Wayan Yuli Andari (Magister of Linguistic, Postgraduated Program, Universitas Warmadewa, 2019)
The aim of this research is to explain the intrinsic elements and the moral form of the story contained in Tarian Bumi novel by Oka Rusmini (2007). The data of this research were obtained from a novel entitled “Tarian Bumi” by Oka Rusmini (2007). Data were collected by observation method and note-taking technique. The collected data were analyzed using the theory of the Intrinsic Fiction Element (Nurgiyantoro, 2015) and the Moral Value theory in Fiction (Nurgiyantoro, 2009). The results of the analysis are presented using informal methods. Based on the analysis that were conducted the intrinsic elements contained in the novel Tarian Bumi are divided into themes, plots, characters, background, point of view, and language. The form of moral values contained in the novel Tarian Bumi is distinguished into a human relationship with itself, human relationship with God, human relationships with other human beings, and human relations with the environment is manifested with social life. The moral value contained in the novel is a reflection of Balinese people’s life that clings to the concept of Tri Hita Karana.